Novel Schiff Base Complexes of 2-hydroxy-1-naphthalidene Oxalyldihydrazone - Dwivedi, D.K.; Shukla, R.K.; Shukla, B.K. (Asian Journal of Chemistry, 2010)
Polymerization reactions involving the formation of Schiff base metal complexes have been described. Schiff base acts as hexadentate and oxobridged binuclear 2 : 1 polymeric structure is proposed with the help of analytical, magnetic, thermal and spectral studies. The metal ion is the bridging unit between the donor sites of the ligand and the polymeric chain grows through consecutive ligand-metal linkages.